Wound drainage after total hip arthroplasty - Golovakha, Maxim; Kirichenko, Vadim; Gritsenko, Alexandra; Belykh, Evgeniy; Titarchuk, Rostislav; Kudin, Stanislav; Didenko, Inna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2020)
Diseases and injuries of the hip joint take a significant place in the structure of orthopaedic pathology. Total hip arthroplasty is the main treatment method of the hip joint osteoarthritis of the III–IV stages and fractures of the femoral neck in the elderly people. Objective: to analyze the effectiveness of the postoperative wound management after total hip arthroplasty without draining. Methods: a group of 140 patients (age — from 45 to 78 years) who underwent total hip arthroplasty in the period from the beginning of 2017 to April 2019 was sampled for this study. Diagnosis: hip joint osteoarthritis of the III–IV stages, aseptic necrosis of the femoral head, rheumatoid arthritis and the femoral neck fracture. The patients were divided into groups: I — the wound was drained, II — the postoperative wound was without drainage. The groups did not differ in age, sex, body mass index and distribution of diagnosis. Results: blood loss during the operation did not differ and was equal in group I — (367.59 ± 16.19) ml, II — (351.6 ± 7.97) ml. The count of erythrocytes was significantly higher in group I, which characterizes less blood loss after surgery. Prior to surgery, ESR and CRP levels did not differ significantly in both groups. After the surgery and at discharge, we noted significantly lower markers of the inflammation in the I group of patients. The maximum intense of the pain according to VAS scale was 5 points for patients of the Ist group and 9 points in the IInd group. Body temperature in patients of the Ist group elevated up to 37.7°C, II — 39.4°C. There were no differences in the timing of postoperative wound healing. Patients were activated for the next day after the surgery. Patients in group I were discharged from the hospital on average of 2 days earlier than group II. Conclusions: in the group of patients without joint draining revealed faster normalization of erythrocytes, CRP and ESR, low intensity of postoperative pain according to VAS, shortened hospital stay.